Effects of the Administration of Coconut (Cocos nucifera) Water and Urea Fertilizer in Various Rates on the Growth and Production of Pakcoy (Brassica juncea L.) - Tarzan Purba; Octavianus Lumban Tobing; Setyono Setyono (JURNAL AGRONIDA, 2018)
Pakcoy (Brassica juncea L.) is a leaf vegetable that requires sufficient nutrients for growth and development to produce maximum production. This study aims to determine the effect of pakcoy watering using coconut water and giving various doses of urea fertilizer to the growth and yield of pakcoy plants. This study used a factorial complete randomized design consisting of two factors. The first factor is the supply of coconut water which consists of four levels of treatment namely without coconut water (A1), volume of coconut water 100 ml (A2), volume of coconut water 150 ml (A3), volume of coconut water 200 ml (A4). The second factor was urea fertilizer which consisted of four treatment levels, namely without urea (N1), urea 0.2 gr (N2), urea 0.4 gr (N3), urea 0.6 gr (N4). The results of this study indicate that the watering of coconut water and the giving of various doses of urea fertilizer affect plant height at the 5th and 6th week, the number of leaves at the 5th and 6th week, leaf area, canopy width at the 5th and 6th week, leaf wet weight, leaf dry weight, root wet weight and root dry weight. The interaction between coconut water and urea fertilizer did not affect all observed variables.Key words: Brassica juncea, coconut water, urea, stover weight, growth.